JUSTICE DYNAMICS IN THE USMAN TURKEY - firdaus firdaus (Menara Ilmu, 2020)
The Ottoman court was a legacy of the Bani Seljuq dynasty, which was militant based on multi-sectarian Islamic Sharia. However, after the period of Sultan Salim I (1511-1520). Basically, legal products must not be in conflict with Islamic Shari'ah and must be examined first by Syaik al-Islam before laws and laws are enacted. With a literature study comparing with the descriptive analysis approach, it was found that the Ottoman Turks slowly underwent renewal that led to the elimination of Islamic sharia in civil and criminal terms while a small part of civil law is still maintained through the codification of law in the majallah al-Ahkam al-Adliyah. Keywords: Dynamics, Ottoman Turkey, Justice